2014
DOI: 10.4314/sajas.v43i5.9
|View full text |Cite
|
Sign up to set email alerts
|

The novel use of “point of care” devices to evaluate transport duration on selected pork quality parameters

Abstract: Point-of-care (POC) devices were used to measure plasma metabolic substrates in pigs subjected to stressful conditions. These were then related to the meat pH, drip loss and carcass temperature. Forty Large White x Landrace pigs (20 females and 20 males) weighing approximately 67 ± 6.5 kg were used in the study. Twenty of the pigs were subjected to a stressful regimen for two hours and the other 20 pigs were transported for 15 minutes from their pens directly to the abattoir. Salivary cortisol, plasma glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In addition, the steers' standing position throughout transportation may be related to the short distance travelled to the abattoir (120 km), while their standing in lairages may have been due to discomfort in a new exposure with concrete and wet floors (caused by rain). Seshoka et al (2013) reported an increase in salivary cortisol level during shorter distances travelled than longer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the steers' standing position throughout transportation may be related to the short distance travelled to the abattoir (120 km), while their standing in lairages may have been due to discomfort in a new exposure with concrete and wet floors (caused by rain). Seshoka et al (2013) reported an increase in salivary cortisol level during shorter distances travelled than longer.…”
Section: Discussionmentioning
confidence: 99%
“…Abattoir managers increasingly monitor workers to improve animal handling and reduce the sources of stress. However, the behaviour of animals must be observed, and saliva, blood and urine samples collected to determine the hormonal-enzymatic and HSP expression (O'Connor et al, 2000;Ndou et al, 2011;Seshoka et al, 2013) in order to examine whether the precautionary measures are effective. Various methods are used to assess the welfare of animals using non-invasive assessment (Boissy et al, 2007;Geiger, 2013).…”
Section: Non-invasive Assessment Of Methods Of Stressmentioning
confidence: 99%
“…However, the use of cortisol as an indicator of stress requires caution. Cortisol levels may change because of several factors, such as types and severity of stressors, circadian rhythms, the blood-sampling method and non-aversive events (Trevisi et al, 2005;Grandin, 2013;Seshoka et al, 2013). An increase in cortisol concentration was observed in transported lambs because of the unloading, handling and bleeding procedure (Tadich et al, 2009).…”
Section: Figurementioning
confidence: 99%
“…En 2003, Leheska concluyó que los tiempos de transporte prolongado reducen la presencia de carne PSE, lo que mejora la calidad de esta, al compararlos con viajes de 30 minutos (50). De igual manera, algunos estudios han mostrado que los viajes de corta duración generan mayores cambios en la temperatura de la canal, la pérdida por goteo y el pH (48,(51)(52)(53)(54).…”
Section: Efecto Del Transporte En El Bienestar Animalunclassified